A Comprehensive Review on Potential In Silico Screened Herbal Bioactive Compounds and Host Targets in the Cardiovascular Disease Therapy. - Zarenezhad, Elham; Hadi, Ali Tareq; Nournia, Ensieh; Rostamnia, Sadegh; Ghasemian, Abdolmajid; Cherstvy, Andrey (BioMed Research International, 2024)
Herbal medicines (HMs) have deciphered indispensable therapeutic effects against cardiovascular disease (CVD) (the predominant cause of death worldwide). The conventional CVD therapy approaches have not been efficient and need alternative medicines. The objective of this study was a review of herbal bioactive compound efficacy for CVD therapy based on computational and in silico studies. HM bioactive compounds with potential anti‐CVD traits include campesterol, naringenin, quercetin, stigmasterol, tanshinaldehyde, Bryophyllin A, Bryophyllin B, beta‐sitosterol, punicalagin, butein, eriodyctiol, butin, luteolin, and kaempferol discovered using computational studies. Some of the bioactive compounds have exhibited therapeutic effects, as followed by in vitro (tanshinaldehyde, punicalagin, butein, eriodyctiol, and butin), in vivo (gallogen, luteolin, chebulic acid, butein, eriodyctiol, and butin), and clinical trials (quercetin, campesterol, and naringenin). The main mechanisms of action of bioactive compounds for CVD healing include cell signaling and inhibition of inflammation and oxidative stress, decrease of lipid accumulation, and regulation of metabolism and immune cells. Further experimental studies are required to verify the anti‐CVD effects of herbal bioactive compounds and their pharmacokinetic/pharmacodynamic features.